Impact of Rule Governance Mechanism on Project Performance in Public Rental Housing PPP Projects: Control Rights as a Moderating Variable - Dan Liu; Wenfeng Mo; Chuanbin Yin (Discrete Dynamics in Nature and Society)
Exploring the relationship among rule governance mechanism, project control rights allocation, and project performance in public-private partnership (PPP) projects is of great significance for optimizing control rights allocation and governance mechanism to improve project performance of PPP projects. Previous studies have mainly focused on the impact of contractual governance or rule-based governance on the performance of PPP projects, and the research on the allocation of project control rights into the analysis framework is insufficient. The goal of this study is to explore the moderating effect of the allocation of project control rights on the project’s rule mechanism affecting project performance. Based on the theoretical analysis and literature review, three hypotheses are put forward, and the hypotheses are tested by structural equation model using the large sample data collected by questionnaire survey. This study shows that both the rule governance mechanism and project control right allocation have a positive impact on project performance, and the allocation of project control right has a negative moderating effect on the impact of rule governance mechanism on project performance. The public characteristics of PPP projects determine that it is inappropriate for social capital to have too much project control rights. The degree of project control rights owned by social capital should be balanced with the rule governance in the dynamic management process.